Microstructure and Mechanical Properties of Additively Manufactured Ni-Al Bronze Parts Using Cold Metal Transfer Process - Wang, Rongcheng; Zhao, Yang; Chang, Qing; Yin, Fengshi; Wang, Xiaoming; Wang, Wenyu; Ren, Zhiqiang; Han, Guofeng (Frontiers in Materials, 2021)
In this paper, the microstructure and mechanical properties of the SG-CuAl8Ni6 Ni-Al bronze straight wall were studied, which was fabricated by the cold metal transfer (CMT) arc additive manufacturing technology. This Ni-Al bronze cladding layer of SG-CuAl8Ni6 is composed mainly of α-Cu, residual β phase, rich Pb phase and κ phase. The microstructure of this multilayer single-channel Ni-Al bronze straight wall circulating presents the overall periodic law, which changes from fine cellular crystals, columnar crystals to dendritic crystals with the increase of the distance from the substrate. The Vickers hardness value of the Ni-Al bronze straight wall decreases with the distance of substrate are between 155 and 185 HV0.5. The microhardness and elastic modulus of the Ni-Al bronze specimen are 1.57 times and 1.99 times higher than these of the brass matrix, respectively. The ultimate tensile strength (UTS) of the straight wall in the welding direction and 45° downward-sloping is greater than that of about 550 MPa in the stacking direction, and the elongation value in the welding direction is the highest. With the increase in interlayer temperature, the grain size increased gradually, and the tensile strength decreases slightly.